Intrathecal or intraventricular therapy for post-neurosurgical Gram-negative meningitis: matched cohort study. (January 2016) - Shofty, B.; Neuberger, A.; Naffaa, M.E.; Binawi, T.; Babitch, T.; Rappaport, Z.H.; Zaaroor, M.; Sviri, G.; Paul, M.
Abstract: Gram-negative post-operative meningitis due to carbapenem-resistant bacteria (CR-GNPOM) is a dire complication of neurosurgical procedures. We performed a nested propensity-matched historical cohort study aimed at examining the possible benefit of intrathecal or intraventricular (IT/IV) antibiotic treatment for CR-GNPOM. We included consecutive adults with GNPOM in two centres between 2005 and 2014. Patients receiving combined systemic and IT/IV treatment were matched to patients receiving systemic treatment only. Matching was done based on the propensity of the patients to receive IT/IV treatment. We compared patient groups with 30-day mortality defined as the primary outcome. The cohort included 95 patients with GNPOM. Of them, 37 received IT/IV therapy in addition to systemic treatment (22 with colistin and 15 with amikacin), mostly as initial therapy, through indwelling cerebrospinal fluid drains. Variables associated with IT/IV therapy in the propensity score included no previous neurosurgery, time from admission to meningitis, presence of a urinary catheter and GNPOM caused by carbapenem-resistant Gram-negative bacteria. Following propensity matching, 23 patients given IT/IV therapy and 27 controls were analysed. Mortality was significantly lower with IT/IV therapy: 2/23 (8.7%) versus 9/27 (33.3%), propensity-adjusted OR 0.19, 95% CI 0.04–0.99. Death or neurological deterioration at 30 days, 14-day and in-hospital mortality were lower with IT/IV therapy (OR <0.4 for all) without statistically significant differences. Among patients discharged alive, those receiving IT/IV therapy did not experience more neurological deterioration. Serious adverse events with IT/IV therapy were not documented. Our results support the early use of IT antibiotic treatment for CR-GNPOM when a delivery method is available.